Implementation of GOLD consensus report in real life: results from the Velletri-Lariano (VELA) cohort - De Filippi, G.; Lallini, M.; De Riggi, G.; Marchetti, G.; Dimartino, C.M.; Russetti, A.M.; Ferrari, E.; Pistelli, R.; Magnoni, M.S.; Riparbelli, M.; Rizzi, A.; Angeletti, P. (Multidisciplinary Respiratory Medicine, 2017)
Background: COPD is one of the leading causes of morbidity and mortality. Pharmacotherapy improves quality of life and reduces exacerbations although low adherence with prescribed treatments may represent a barrier to optimal disease management. The first objective of this paper is to report the distribution of COPD patients according to GOLD categories, in a sample of patients from a cohort study in an area of the Latium region in Italy. The second objective is to evaluate the agreement between the distributions of severity obtained from the HCPs and the experts included in the study board (Board). Methods: COPD patients were given a card to collect demographic and clinical data at baseline. Information in those cards was independently evaluated by HCPs and Board to include each patient into one of the four GOLD categories. Results: In a sample of 187 stable COPD patients, 59% male, mean age 70 year, the distribution of GOLD categories according to the Board was: 6% A, 34% B, 2% C, and 58% D. A discrepancy in GOLD classification was observed between the study board and field-based HCPs, regarding more than 50% of the patients, with a clear trend to underestimate the frequency of patients in D level (21%) and to overestimate the frequency in C level (21%). Conclusions: These results describe for the first time the distribution of COPD patients in an Italian cohort according to the GOLD categories, with the highest frequencies in levels B and D. The misclassification from HCPs may impact the therapeutic approach and the clinical outcomes.